Literacy Skills of Digital-Age Primary School Students in Mandailing Natal Regency - Parulian Siregar; Naimah Naimah; Sri Sumarni; Erni Munastiwi (Journal of Integrated Elementary Education)
This research aimed to investigate literacy skills, the underlying causes of low literacy levels, and the implications for primary school students in the digital age. The researcher employed a qualitative field research methodology, collecting data through participatory observation, in-depth interviews, and the utilization of Google Forms. The data analysis involved systematic reduction, presentation of findings, and the formulation of conclusions, all while employing coding techniques and categorizing themes. The findings indicate that the literacy skills of elementary school students in Indonesia remain significantly underdeveloped. A considerable number of students encounter difficulties in comprehending simple texts, organizing their thoughts in writing, and understanding the material presented by teachers. Additionally, they face challenges in grasping fundamental mathematics and science concepts, as well as effectively utilizing digital tools in their educational experiences. Several factors contribute to the observed low literacy levels, including a lack of supportive familial environments, inadequate integration of technology in educational settings, ineffective instructional models, and limited access to digital resources and training. The repercussions of insufficient literacy skills are evident in students’ difficulties in solving problems, accessing information, and articulating their thoughts, both verbally and in written form. To mitigate this issue, it is recommended that educators integrate digital tools into their pedagogical strategies. This can be achieved through the implementation of project-based learning and the use of educational podcasts disseminated via online platforms.